Preoperative Geriatric Nutritional Risk Index: A predictive and prognostic factor in patients with pathological stage I non-small cell lung cancer. (December 2017) - Shoji, Fumihiro; Matsubara, Taichi; Kozuma, Yuka; Haratake, Naoki; Akamine, Takaki; Takamori, Shinkichi; Katsura, Masakazu; Toyokawa, Gouji; Okamoto, Tatsuro; Maehara, Yoshihiko
Abstract: Background: Surgical outcomes of early-stage non-small cell lung cancer (NSCLC) are poor. The Geriatric Nutritional Risk Index (GNRI) is a useful parameter for evaluating nutritional status. We aimed to investigate if preoperative GNRI could be a predictive factor for pathological stage I NSCLC patients. Patients and methods: We retrospectively selected 141 consecutive pathological stage I NSCLC patients treated from August 2005 to August 2010. We analyzed their preoperative GNRI in univariate and multivariate Cox regression analyses for postoperative recurrence-free survival (RFS). Results: A preoperative abnormal GNRI was significantly associated with postoperative recurrence ( P  = 0.0107). Univariate analyses showed that serum carcinoembryonic antigen (CEA) levels ( P  = 0.0013), preoperative serum albumin level ( P  < 0.0001), preoperative GNRI ( P  = 0.0009), pleural invasion ( P  < 0.0001) and blood vessel invasion ( P  = 0.0137) significantly affected RFS. In multivariate analysis, preoperative GNRI ( P  = 0.0084), CEA level ( P  = 0.0031), preoperative serum albumin level ( P  = 0.0041) and pleural invasion ( P  = 0.0018) were independent prognostic factors. In Kaplan–Meier analysis of RFS, cancer-specific survival (CS), and overall survival (OS) by preoperative GNRI, the abnormal GNRI group had significantly shorter RFS, CS, and OS (5-year RFS, CS, and OS: 52.81% vs. 89.15%; P  < 0.0001, 81.73% vs. 94.73%; P  = 0.0014 and 50.84% vs. 89.57%; P  < 0.0001, log-rank test, respectively). Conclusions: Preoperative GNRI is a novel prognostic factor for pathological stage I NSCLC patients, which can identify high-risk patients for postoperative recurrence and cancer-related death. Highlights: The GNRI is based on two parameters including serum albumin and body weight. We analyzed p-stage I NSCLC patients to investigate effects of preoperative GNRI. Preoperative GNRI was significantly associated with postoperative recurrence. Preoperative abnormal GNRI group had significantly shorter RFS, CS, and OS. Preoperative GNRI is a simple and novel prognostic factor.